Conspiracy. A Conceptual Genealogy (Thirteenth to Early Eighteenth Century) - Saucedo, Víctor (Historia del Derecho, 2017)
This book focuses on the development of the law of conspiracy in England from the thirteenth to the early eighteenth century. The historiography of the law of conspiracy has adopted an unmistakably doctrinal approach to this topic which has produced a treasure trove of legal sources. By borrowing concepts from cognitive linguistics, this research will shed light upon new aspects of these sources that the doctrinal approach could not reveal. It will show how certain conducts were lexicalized as a conspiracy in the Middle Ages. It will also show how these terms are involved in the lexicalization of the crime of treason and how through a process of conceptual blending the action upon the case in the nature of conspiracy rose as an action separate from the medieval conspiracy. Finally, it will be seen how the modern offense of conspiracy emerged out of the process of conceptual blending through analogies with treason and the action upon the case in the nature of conspiracy.------ Este libro se centra en la genealogía del delito de conspiración en Inglaterra desde el siglo XIII hasta comienzos del XVIII. La historiografía acerca del mismo ha sido de carácter marcadamente doctrinal, aunque ha producido un valioso acopio de fuentes. Haciendo uso de conceptos de la lingüística cognitiva, esta investigación revela aspectos de la genealogía del concepto de conspiración que el enfoque doctrinal no podía percibir. Se muestra cómo ciertas conductas fueron lexicalizadas como conspiración en la Edad Media, cómo el mismo término aparece en la conceptualización del delito de traición y cómo a través de un proceso de integración conceptual se produjo la action upon the case in the nature of conspiracy diferente de la conspiración medieval. Finalmente, también se verá cómo el moderno sentido de conspiración surgió a través del mismo proceso de integración conceptual que permitía establecer analogías con el delito de traición, así como con la action upon the case in the nature of conspiracy.